PENGELOLAAN RETRIBUSI PARKIR YANG EFEKTIF DAN EFISIEN DI JL. SINGABANA DAN JL. AGUS SALIM KECAMATAN PULAU LAUT UTARA KABUPATEN KOTABARU - Eny Sri Harmeny; Fifi Swandari; Dian Masita Dewi (Universitas Lambung Mangkurat, 2021)
This study aims to determine and analyze the effectiveness and efficiency parking retribution management on Singabana Street and Agus Salim Street, as well as the obstacles faced and strategies that should be taken by the Regional Government to increase retribution revenue in Kotabaru Districts. This research method uses quantitative descriptive with the primary data source is interviews with four respondents and the secondary data source is the revenue plan, revenue realization and costs incurred by the local government from 2015 to 2019 from the Transportation Office on Kotabaru Districts. Data analysis used ratio analysis with effective and efficient value interpretation and descriptive analysis. The results of the study state that parking retribution from 2015 to 2019 on Singabana Street and Agus Salim Street is less effective, but quite efficient. The obstacles faced are the limited staff for supervision, limited parking space and the difficulty of applying sanctions to both managers and illegal parking. The strategy taken is adding employees, coordinating with related parties, optimizing and increasing the number of parking spots, and imposing sanctions or rewards indiscriminately.